Parameterization Interactions in Global Aquaplanet Simulations. (9th February 2018) - Bhattacharya, Ritthik; Bordoni, Simona; Suselj, Kay; Teixeira, João
Abstract: Global climate simulations rely on parameterizations of physical processes that have scales smaller than the resolved ones. In the atmosphere, these parameterizations represent moist convection, boundary layer turbulence and convection, cloud microphysics, longwave and shortwave radiation, and the interaction with the land and ocean surface. These parameterizations can generate different climates involving a wide range of interactions among parameterizations and between the parameterizations and the resolved dynamics. To gain a simplified understanding of a subset of these interactions, we perform aquaplanet simulations with the global version of the Weather Research and Forecasting (WRF) model employing a range (in terms of properties) of moist convection and boundary layer (BL) parameterizations. Significant differences are noted in the simulated precipitation amounts, its partitioning between convective and large‐scale precipitation, as well as in the radiative impacts. These differences arise from the way the subcloud physics interacts with convection, both directly and through various pathways involving the large‐scale dynamics and the boundary layer, convection, and clouds. A detailed analysis of the profiles of the different tendencies (from the different physical processes) for both potential temperature and water vapor is performed. While different combinations of convection and boundary layer parameterizations can lead to different climates, a key conclusion of this study is that similar climates can be simulated with model versions that are different in terms of the partitioning of the tendencies: the vertically distributed energy and water balances in the tropics can be obtained with significantly different profiles of large‐scale, convection, and cloud microphysics tendencies. Key Points: To understand parameterization interactions in a GCM, aquaplanet simulations are performed in WRF using a suite of convection/BL schemes While the generated mean climates have qualitative similarities, differences are seen in cloud and precipitation behavior (amount & types) These differences arise from how the BL scheme interacts with convection, both directly and via large‐scale dynamics and microphysics